Neuronal surface and glutamic acid decarboxylase autoantibodies in Nonparaneoplastic stiff person syndrome. - Chang, T; Alexopoulos, H; Mcmenamin, M; Carvajal-González, A; Alexander, S; Deacon, R; Erdelyi, F; Szabó, G; Gabor, S; Lang, B; Blaes, F; Brown, P; et al. (2013)
IMPORTANCE: High titers of autoantibodies to glutamic acid decarboxylase (GAD) are well documented in association with stiff person syndrome (SPS). Glutamic acid decarboxylase is the rate-limiting enzyme in the synthesis of γ-aminobutyric acid (GABA), and impaired function of GABAergic neurons has been implicated in the pathogenesis of SPS. Autoantibodies to GAD might be the causative agent or a disease marker. OBJECTIVE: To investigate the characteristics and potential pathogenicity of GAD autoantibodies in patients with SPS and related disorders. DESIGN: Retrospective cohort study and laboratory investigation. SETTING: Weatherall Institute of Molecular Medicine, University of Oxford. PARTICIPANTS: Twenty-five patients with SPS and related conditions identified from the Neuroimmunology Service. EXPOSURES: Neurological examination, serological characterization and experimental studies. MAIN OUTCOMES AND MEASURES: Characterization of serum GAD antibodies from patients with SPS and evidence for potential pathogenicity. RESULTS: We detected GAD autoantibodies at a very high titer (median, 7500 U/mL) in 19 patients (76%), including all 12 patients with classic SPS. The GAD autoantibodies were high affinity (antibody dissociation constant, 0.06-0.78 nmol) and predominantly IgG1 subclass. The patients’ autoantibodies co-localized with GAD on immunohistochemistry and in permeabilized cultured cerebellar GABAergic neurons, as expected, but they also bound to the cell surface of unpermeabilized GABAergic neurons. Adsorption of the highest titer (700 000 U/mL) serum with recombinant GAD indicated that these neuronal surface antibodies were not directed against GAD itself. Although intraperitoneal injection of IgG purified from the 2 available GAD autoantibody–ositive purified IgG preparations did not produce clinical or pathological evidence of disease, SPS and control IgG were detected in specific regions of the mouse central nervous system, particularly around the lateral and fourth ventricles. CONCLUSIONS AND RELEVANCE: Autoantibodies to GAD are associated with antibodies that bind to the surface of GABAergic neurons and that could be pathogenic. Moreover, in mice, human IgG from the periphery gained access to relevant areas in the hippocampus and brainstem. Identification of the target of the non-GAD antibodies and peripheral and intrathecal transfer protocols, combined with adsorption studies, should be used to demonstrate the role of the non-GAD IgG in SPS.